Midlife Lifestyle Activities Moderate APOE ε4 Effect on in vivo Alzheimer’s Disease Pathologies - Jeon, So Yeon; Byun, Min Soo; Yi, Dahyun; Lee, Jun-Ho; Ko, Kang; Sohn, Bo Kyung; Lee, Jun-Young; Ryu, Seung-Ho; Lee, Dong Woo; Shin, Seoung A; Kim, Yu Kyeong; Kang, Koung Mi; et al. (Frontiers in Aging Neuroscience, 2020)
This study aimed to investigate whether the midlife cognitive activity and physical activity moderate the relationship between apolipoprotein Eε4 (APOE4) and in vivo Alzheimer’s disease (AD) pathologies. In total, 287 non-demented older adults (mean age 72 years) from the Korean Brain Aging Study for the Early diagnosis and prediction of Alzheimer’s disease cohort were included. Participants underwent a comprehensive clinical assessment including the evaluation for midlife CA and physical activity, [11C]-Pittsburgh-Compound-B-positron emission tomography (PET), [18F]-fluorodeoxyglucose PET, structural magnetic resonance imaging (MRI), and APOE genotyping. We used linear regression and regression-based mediated-moderation models for statistical analyses. Neither midlife cognitive activity nor physical activity moderated the effect of APOE4 on β-amyloid (Aβ) retention itself. Midlife cognitive activity significantly moderated the effect of APOE4 on hippocampal volume [B (SE) = − 627.580 (252.327), t = −2.488, p = 0.014]: APOE4 carriers had smaller hippocampal volume than non-carriers at relatively high cognitive activity state (p = 0.004), but not at relatively low cognitive activity condition (p = 0.937). Midlife physical activity significantly moderated the effect of Aβ retention, which was closely related to APOE4, on AD-signature region cerebral glucose metabolism [AD-CM; B (SE) = 0.004 (0.002), t = 2.030, p = 0.043]: higher Aβ accumulation was associated with lower AD-CM in relatively low physical activity condition (p < 0.001), whereas no such association was observed in relatively high physical activity state (p = 0.791). The findings suggest that high midlife cognitive activity may accelerate hippocampal atrophy induced by APOE4, whereas high midlife physical activity may delay AD-related cerebral hypometabolism by weakening the influence of APOE4-associated Aβ retention.